2021
DOI: 10.3389/fpsyg.2021.683569
|View full text |Cite
|
Sign up to set email alerts
|

Delivering the Multisensory Experience of Dining-Out, for Those Dining-In, During the Covid Pandemic

Abstract: In many parts of the world, restaurants have been forced to close in unprecedented numbers during the various Covid-19 pandemic lockdowns that have paralyzed the hospitality industry globally. This highly-challenging operating environment has led to a rapid expansion in the number of high-end restaurants offering take-away food, or home-delivery meal kits, simply in order to survive. While the market for the home delivery of food was already expanding rapidly prior to the emergence of the Covid pandemic, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…That said, we still cannot ignore the advantages of digital commensality. For one thing, considering the health risk and loneliness caused by lockdown during the recent COVID-19 crisis ( Holmes et al, 2020 ), cloud-based commensality via videoconferencing tools has been identified as a safe and efficient alternative to social gatherings and loneliness regulation ( Ceccaldi et al, 2020 ; Spence et al, 2021 ). For another, in-person and cloud-based commensality could both elicit the feeling of being accompanied by family or friends ( Cruwys et al, 2015 ; Ceccaldi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…That said, we still cannot ignore the advantages of digital commensality. For one thing, considering the health risk and loneliness caused by lockdown during the recent COVID-19 crisis ( Holmes et al, 2020 ), cloud-based commensality via videoconferencing tools has been identified as a safe and efficient alternative to social gatherings and loneliness regulation ( Ceccaldi et al, 2020 ; Spence et al, 2021 ). For another, in-person and cloud-based commensality could both elicit the feeling of being accompanied by family or friends ( Cruwys et al, 2015 ; Ceccaldi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As will be highlighted below, each one of the various approaches to sonic seasoning has their respective strengths and weaknesses in terms of the efficiency, cost of development/implementation, etc. Taken together, the various examples reviewed here help to illustrate the growing commercial relevance of, and interest in, sonic seasoning research (see also Mickiewicz, 2014 ; Roncero-Menendez, 2015 ; Spence, 2020a ; Spence et al, 2021 ; Wang et al, 2019c ).…”
Section: Introductionmentioning
confidence: 81%
“…Alternatively, one might consider a “TastEQ” feature in an application that could tweak the frequency and pitch of selected tracks to enhance the relevant taste (raising the pitch/frequency to add sweetness, or lowering it for those who want a little more bitterness, similar to the Beck’s Frequency case presented earlier). There is also the opportunity to go beyond auditory only stimulation, using audiovisual digital activations that may allow for more pronounced sensory manipulation (e.g., see Wang and Spence, 2015b ; McGregor, 2017 ), perhaps even paring meals with shows on digital channels such as Netflix or Amazon Prime (as discussed briefly in Spence et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations